2022
DOI: 10.37905/jji.v4i1.13411
|View full text |Cite
|
Sign up to set email alerts
|

Pengukuran Tingkat Usability Sistem Aplikasi e-Rapor Menggunakan Metode Usability Testing dan SUS

Abstract: e-Rapor merupakan aplikasi yang dikembangkan oleh Direktorat Pembinaan SMK sebagai bagian dari hasil representasi evaluasi terhadap proses pendidikan yang diterapkan melalui proses perencanaan, penilaian, dan pelaporan hasil evaluasi belajar peserta didik pada satuan pendidikan. Dari hasil observasi awal terhadap penggunaan aplikasi, masih terdapat kendala yang dialami pada saat proses penginputan perencanaan pengetahuan, perencanaan keterampilan, penilaian pengetahuan dan penilaian keterampilan peserta didik.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…LITERATURE REVIEW Several previous studies have used usability testing to test the applications built by them. From these studies, it is stated that usability testing aims to determine whether the application built has answered the user's needs or not (Buana & Nurina Sari, 2022;Fatah, 2020;Murti, 2020;Nurhadryani et al, 2013;Rizki et al, 2021;Surono Wibowo, 2016;Tuloli et al, 2022;Yuliyana et al, 2019). Then studies related to usability but focused on using the user experience questionnaire method were carried out by Firmansyah, (2018); Junita Maulani & Reza Perdanakusuma, (2021) In their research, they concluded that the Use Questionnaire could be used to measure the usability of a software/application interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LITERATURE REVIEW Several previous studies have used usability testing to test the applications built by them. From these studies, it is stated that usability testing aims to determine whether the application built has answered the user's needs or not (Buana & Nurina Sari, 2022;Fatah, 2020;Murti, 2020;Nurhadryani et al, 2013;Rizki et al, 2021;Surono Wibowo, 2016;Tuloli et al, 2022;Yuliyana et al, 2019). Then studies related to usability but focused on using the user experience questionnaire method were carried out by Firmansyah, (2018); Junita Maulani & Reza Perdanakusuma, (2021) In their research, they concluded that the Use Questionnaire could be used to measure the usability of a software/application interface.…”
Section: Introductionmentioning
confidence: 99%
“…Then studies related to usability but focused on using the user experience questionnaire method were carried out by Firmansyah, (2018); Junita Maulani & Reza Perdanakusuma, (2021) In their research, they concluded that the Use Questionnaire could be used to measure the usability of a software/application interface. as well as research specifically using the System Usability Scale, it was found that the System Usability Scale method can be used to test websites/applications in a structured way (Aprilia et al, 2015;Buana & Nurina Sari, 2022;Tuloli et al, 2022). This indicates that existing methods can be used to improve the experience and satisfaction of the user in opening the website.…”
Section: Introductionmentioning
confidence: 99%
“…Efektivitas harus dinilai atas dasar tujuan yang bisa dilaksanakan, bukan atas dasar konsep tujuan yang maksimum. Efektivitas diukur dengan menggunakan standar sesuai dengan acuan Litbang Depdagri (1991) seperti pada Tabel 1 [5]. Keterangan : N = Jumlah total tugas (gol) R = Jumlah pengguna nij = Hasil tugas i oleh pengguna j; jika pengguna berhasil menyelesaikan tugas, maka Nij = 1, jika tidak, maka Nij = 0 ,tij = Waktu yang dihabiskan oleh pengguna j untuk menyelesaikan tugas i. Jika tugas tidak berhasil diselesaikan, maka waktu diukur hingga saat pengguna berhenti dari tugas .…”
Section: Teknik Performance Measuementunclassified
“…Selanjutnya hasil rata-rata waktu yang dibutuhkan untuk mengerjakan task scenario tersebut diinterpretasikan menggunakan range waktu pada indikator time behavior seperti yang terdapat pada Tabel 2 untuk menentukan durasi waktu yang digunakan pengguna dalam penyelesaiaan task sehingga dapat diketahui hasil pengukuran tingkat efisiensi dari aplikasi [5].…”
Section: Teknik Performance Measuementunclassified
See 1 more Smart Citation